Novel cerium-iron-boron rare earth magnet and three-stage aging coercive force improving process

By adding Cu and T i to the formula of cerium-ferroboron magnets, and using Ce instead of part Pr-Nd, the cerium content is increased, and the three-stage aging treatment process is adopted, the problem of limited temperature range applicable to cerium-ferroboron magnets is solved, and higher magnetic properties and a wider temperature application range are achieved.

CN119560252APending Publication Date: 2025-03-04ZHONGXI YINUOWEI (SHANDONG) MAGNETIC MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411740556.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The low cerium content of existing cerium ferroboron magnets leads to a limited temperature range, which makes it difficult to meet the magnetic performance requirements in high temperature environments.

Method used

By adding Cu and T i to the formula of cerium-ferroboron magnets and using Ce instead of part Pr-Nd, the cerium content is increased, and the microstructure of the magnet is optimized by using a three-stage aging process.

Benefits of technology

The corrosion resistance, temperature resistance and coercivity of magnets are improved, the applicable temperature range is expanded, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560252A_ABST
    Figure CN119560252A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rare earth magnetic materials, in particular to a novel cerium-iron-boron rare earth magnet and a three-stage aging coercive force improving process. The magnet comprises the following components in percentage by weight: 16 to 24 percent of Pr-Nd, 6 to 12 percent of Ce, 0 to 0.5 percent of Zr, 0 to 1 percent of Al, 0 to 0.5 percent of Cu, 0.9 to 1.1 percent of B, 0 to 1.2 percent of Co, 0 to 0.3 percent of Ti, 0 to 3 percent of Gd, and the balance of Fe, wherein the Pr-Nd accounts for 16 to 24 percent, the Ce accounts for 6 to 12 percent, the Zr accounts for 0 to 0.5 percent, the Al accounts for 0 to 1 percent, the Cu accounts for 0 to 0.5 percent, the B accounts for 0.9 to 1.1 percent, the Co accounts for 0 to 1.2 percent, the Ti accounts for 0 to 0.3 percent, the gadolinium accounts for 0 to 3 percent, and the balance is Fe. The method comprises the steps of raw material weighing, smelting and sheet casting, hydrogen decrepitation grinding, magnetic powder forming and sintering forming. The technical problem that in the prior art, due to the fact that the cerium content of a cerium-iron-boron magnet is low, the applicable temperature range of the cerium-iron-boron magnet is limited is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth magnetic materials, and in particular to a novel cerium-iron-boron rare earth magnet and a three-level aging process for improving coercivity. Background Art

[0002] Rare earth magnets are alloys composed of rare earth metals (such as samarium, neodymium, etc.) and transition metals (such as cobalt, iron, etc.). These alloys are processed by specific processes to form permanent magnetic materials with excellent magnetic properties. For cerium iron boron magnets among rare earth magnets, the addition of cerium will lead to a decrease in the coercive force, remanence and other properties of the magnets. At present, high-performance magnets can only be prepared using the neodymium iron boron preparation process. However, the price of neodymium among rare earth elements is much higher than that of cerium, making its preparation cost too high.

[0003] In this regard, the patent document with the authorization announcement number CN113643870B discloses a high-performance cerium iron boron magnet and a preparation method thereof. The magnet comprises a main phase alloy and an auxiliary phase alloy, wherein the auxiliary phase alloy accounts for 5 to 10 wt% of the high-performance cerium iron boron magnet; the components of the main phase alloy are (R, Ce) a Fe b M c B d The mass percentage of each component in the main phase alloy is: 29wt%≤a≤32wt%, 0.1wt%≤c≤2wt%, 0.9wt%≤d≤1wt%, and the rest is b, wherein Ce is the rare earth element cerium, Ce accounts for 1-2wt% in the main phase alloy, R is at least one of the other rare earth elements except cerium; M is at least one of Al, Si, Mg, Ti, V, Cr, Mn, Ni, Co, Cu, Zn, Ga, Zr, Nb, and W; Fe is iron, and B is boron; the components and mass percentages of the auxiliary phase alloy are R' x Fe y M' z B m The mass percentage of each component in the auxiliary phase alloy is: 32wt%≤x≤80wt%, 0.1wt%≤z≤2wt%, 0.3wt%≤m≤1.0wt%, and the rest is y; wherein R' is at least two of the other rare earth elements except Ce and must include Nd and Dy; M' is at least one of Al, Si, Mg, Ti, V, Cr, Mn, Ni, Co, Cu, Zn, Ga, Zr, Nb, and W elements.

[0004] It can be seen that the above-mentioned cerium-iron-boron magnet is prepared by preparing a main phase alloy with low rare earth and high magnetic energy product with added cerium, and adding an auxiliary phase alloy to the main phase alloy to improve the state and promote the increase of coercivity, thereby obtaining a magnet with high magnetic energy product and high coercivity under the condition of adding cerium. However, the cerium content in the above-mentioned cerium-iron-boron magnet is only 1-2wt%. The low cerium content will affect the stability of the magnet at high temperature, thereby causing its magnetic properties to decrease, making the temperature range of the cerium-iron-boron magnet limited. Summary of the invention

[0005] The invention provides a novel cerium iron boron rare earth magnet and a three-level aging process for improving coercivity, so as to solve the technical problem in the prior art that the cerium iron boron magnet has a limited applicable temperature range due to its low cerium content.

[0006] In order to solve the above problems, the novel cerium iron boron rare earth magnet provided by the present invention adopts the following technical solutions:

[0007] A novel cerium-iron-boron rare earth magnet comprises the following components: praseodymium-neodymium (Pr-Nd), cerium (Ce), zirconium (Zr), aluminum (Al), copper (Cu), boron (B), cobalt (Co), titanium (Ti), gadolinium (Gd), and iron (Fe), wherein Pr-Nd: 16-24wt%, Ce: 6-12wt%, Zr: 0-0.5wt%, Al: 0-1wt%, Cu: 0-0.5wt%, B: 0.9-1.1wt%, Co: 0-1.2wt%, Ti: 0-0.3wt%, Gd: 0-3wt%, and the rest is Fe.

[0008] The novel cerium iron boron rare earth magnet provided by the present invention has the following beneficial effects:

[0009] 1. By adding Cu to the formula, the weight loss of the magnet is reduced. The corrosion process of sintered NdFeB alloy is essentially selective corrosion. The chemical properties and distribution state of the neodymium-rich phase are the key factors that determine the corrosion resistance of the NdFeB alloy. After adding Cu, Cu will not replace Fe in the main phase, but melt in the neodymium-rich phase. By changing the composition of the neodymium-rich phase, the corrosion resistance of the magnet is improved, the weight loss of the magnet is reduced, and the cost is reduced. At the same time, the temperature resistance and corrosion resistance of the magnet are enhanced, and the applicable temperature range of the new cerium-iron-boron magnet is expanded;

[0010] 2. By adding Ti to the formula, the intrinsic coercivity of the magnet can be increased, ensuring that the magnet performance is more stable. For sintered NdFeB magnets, the source of its coercivity is mainly demagnetization coupling. The formation of Ti new phase is of great benefit to demagnetization coupling. Therefore, the intrinsic coercivity of the magnet can be increased. At the same time, due to the high melting point of Ti(FeCo)B, it is very beneficial to the uniformity of the magnet microstructure, making the magnet performance more stable.

[0011] 3. Using Ce to replace part of Pr-Nd increases the cerium content, which can not only make the magnetic performance indicators of the magnet meet the national standards, but also save material costs.

[0012] Through the above arrangement, the present invention effectively solves the technical problem in the prior art that the cerium content of the cerium-iron-boron magnet is low, resulting in a limited applicable temperature range.

[0013] In order to solve the above problems, the novel cerium iron boron rare earth magnet provided by the present invention adopts the following technical solutions:

[0014] A three-stage aging process for improving coercivity comprises the following steps:

[0015] S1: Weigh the raw materials: weigh the raw materials according to claim 1 according to weight percentage, wherein Pr-Nd: 16-24wt%, Ce: 6-12wt%, Zr: 0-0.5wt%, Al: 0-1wt%, Cu: 0-0.5wt%, B: 0.9-1.1wt%, Co: 0-1.2wt%, Ti: 0-0.3wt%, Gd: 0-3wt%, and the rest is Fe;

[0016] S2: Melting castings: Put the raw materials in step S1 into a vacuum quick-setting furnace in order, let them stand after they are fully melted, and then cast them into scaly castings. When the casting temperature is lower than 40°C, collect the castings for later use;

[0017] S3: Hydrogen crushing and grinding: using a hydrogen crushing furnace to hydrogen crush the casting to obtain magnetic powder;

[0018] S4: Magnetic powder molding: molding the magnetic powder in a fully automatic magnetic field molding machine to obtain a compact;

[0019] S5: Sintering: The green compact is sintered in a vacuum sintering furnace, the sintering temperature is T1, the sintering time is t1, and the aging treatment is performed after the sintering treatment is completed. The heat treatment temperature of the primary aging treatment is T2, and the heat treatment time is t2. The heat treatment temperature of the secondary aging treatment is T3, and the heat treatment time is t3. The heat treatment temperature of the tertiary aging treatment is T4, and the heat treatment time is t4, wherein T2>T3>T4. After the tertiary aging treatment, the obtained green compact is cooled, and after being cooled to T5, a novel cerium-iron-boron rare earth magnet is obtained.

[0020] The three-stage aging process for improving coercivity provided by the present invention has the following beneficial effects: by performing three-stage aging treatment on the sintered green compact, and making the treatment temperature T2>T3>T4, during the aging treatment process, the microstructure of the magnet can be optimized step by step, which is helpful for fine regulation and directional arrangement of magnetic domains, thereby improving the magnetic energy product, remanence and coercivity of the magnet, and during the aging treatment process, the stress generated inside the green compact during the sintering process can be effectively released, thereby improving its mechanical strength and stability, and preventing the prepared magnet from breaking or deforming due to stress concentration during use. At the same time, during the aging treatment process, the grain boundary structure inside the green compact can be gradually adjusted, thereby improving the stability of the magnet at high temperatures and expanding the temperature application range of the magnet.

[0021] Through the above arrangement, the present invention effectively solves the technical problem in the prior art that the cerium content of the cerium-iron-boron magnet is low, resulting in a limited applicable temperature range.

[0022] Furthermore, the sintering temperature T1 is 1020-1100° C., and the sintering time t1 is 3-5 hours.

[0023] Furthermore, the heat treatment temperature T2 is 870-950°C, the heat treatment time t2 is 2-3h, the heat treatment temperature T3 is 700-800°C, the heat treatment time t3 is 2-4h, the heat treatment temperature T4 is 420-460°C, and the heat treatment time t4 is 4-6h.

[0024] Furthermore, the preheating time of the vacuum rapid solidification furnace is t5, the melting temperature is T6, and the melting time is t6.

[0025] Furthermore, the preheating time t5 is 30 to 40 minutes, the smelting temperature T6 is 1350 to 1550° C., and the smelting time t6 is 40 to 45 minutes.

[0026] Furthermore, after the casting sheet is subjected to hydrogen crushing treatment in a hydrogen crushing furnace to obtain the magnetic powder, the magnetic powder is ground into 2.5-3.5 μm magnetic powder by air flow mill and stirred in a three-dimensional mixer for a stirring time of t7. After the stirring is completed, it is placed in a stainless steel barrel and flushed with high-purity nitrogen for standby use.

[0027] Furthermore, the stirring time t7 is 1 to 3.5 hours.

[0028] Furthermore, the magnetic field strength of the fully automatic magnetic field forming press is B, the forming pressure is P, and the holding time is t8.

[0029] Furthermore, the magnetic field intensity B is 1.8 T, the molding pressure P is 4-8 MPa, and the holding time t8 is 30 s. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] By reading the following detailed description with reference to the accompanying drawings, the above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0031] Figure 1 This is a flow chart of the three-stage aging process for improving coercivity provided by the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Those skilled in the art should know that the embodiments described below are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0033] It should be noted that the main idea of ​​the present invention is: by adding Cu to the formula to reduce the weight loss of the magnet, Cu melts in the neodymium-rich phase, which can improve the corrosion resistance of the magnet, while reducing the cost, enhancing the heat resistance and corrosion resistance of the magnet, and expanding the applicable temperature range of the new cerium-iron-boron magnet; by adding Ti to the formula, the intrinsic coercive force of the magnet can be improved to ensure that the magnet performance is more stable; by using Ce to replace part of Pr-Nd, it is possible to save material costs while ensuring that the magnetic performance indicators of the magnet meet the national standards; by adopting a three-stage aging treatment process, the magnetic domain can be finely controlled, the magnetic energy product, remanence and coercive force of the magnet can be improved, and the stability of the magnet at high temperatures can be further improved, thereby better expanding the temperature application range of the magnet.

[0034] After introducing the basic principle of the present invention, various non-limiting embodiments of the present invention are described in detail below. The number of any element in the drawings is for illustration and not for limitation, and any naming is only for distinction and does not have any limiting meaning.

[0035] In recent years, with the rapid expansion of the application field of NdFeB magnets, the demand for raw materials has become increasingly greater, but due to the high cost of rare earth mining and the increase in national regulatory efforts, its material costs have gradually increased. The proportion of high-priced rare earth elements such as praseodymium, neodymium, holmium, and gadolinium is relatively high, and the cerium content does not exceed 3wt%. Under the current situation of excessive price increases, the price tolerance of the downstream market is relatively limited. Some downstream companies have chosen to use cheaper ferrites or aluminum nickel cobalt, samarium cobalt and other materials to replace the rare earths in the raw materials of NdFeB magnets, which brings greater instability to the NdFeB magnet market. In addition, NdFeB magnet materials are highly brittle and have mixed specifications. They are prone to problems such as missing corners and poor dimensions during the electroplating process. The scrap volume of NdFeB magnets after electroplating is very large. The scrap rate of finished product appearance and size alone is between 2% and 5%. Due to other customer requirements, bad scrapping often occurs. Therefore, reducing the cost of sintered NdFeB magnets is one of the problems that need to be solved urgently.

[0036] At present, there are many domestic manufacturers of NdFeB magnets, and the production processes of NdFeB magnets of different grades are roughly the same. NdFeB magnets of medium and low grades of N38~N48 / 38M~45M are magnet materials with high demand in the current CD-ROM drives, robots, and high-end audio markets. They have high production costs and high energy consumption during the production process. The current conventional manufacturing methods in the industry have the following defects: (1) The use of expensive heavy rare earth elements such as gadolinium, terbium, and dysprosium causes high material costs; (2) Cerium is added alone or in combination, but the amount added cannot exceed 5wt%, otherwise it will not only deteriorate the magnetic properties but also fail to achieve a significant effect of reducing costs.

[0037] In view of the deficiencies in the prior art, the present invention provides a novel cerium-iron-boron rare earth magnet and a three-level aging process for improving coercivity, so that the magnetic properties of the magnet can be guaranteed when the cerium content in the magnet is ≥5wt%.

[0038] The principle and spirit of the present invention are explained in detail below with reference to several representative embodiments of the present invention.

[0039] Embodiments of the novel cerium iron boron rare earth magnet provided by the present invention:

[0040] The novel cerium-iron-boron rare earth magnet comprises the following components: praseodymium-neodymium (Pr-Nd), cerium (Ce), zirconium (Zr), aluminum (Al), copper (Cu), boron (B), cobalt (Co), titanium (Ti), gadolinium (Gd), and iron (Fe), wherein Pr-Nd: 16-24wt%, Ce: 6-12wt%, Zr: 0-0.5wt%, Al: 0-1wt%, Cu: 0-0.5wt%, B: 0.9-1.1wt%, Co: 0-1.2wt%, Ti: 0-0.3wt%, Gd: 0-3wt%, and the rest is Fe.

[0041] The performance of the new type of cerium iron boron rare earth magnet at a test temperature of 20°C is: remanence Br: 12.3~13.8kGs, magnetic coercivity Hcb: 11.5~13.2kOe, intrinsic coercivity Hcj: 12.0~16kOe, maximum magnetic energy product (BH)m: 38~48MGOe, squareness Hk≥98.0%, basically covering the conventional medium and low grades N38~N48 / 38M~45M series.

[0042] Next, a set of specific data is used to compare the performance of the new Cerium Iron Boron rare earth magnet with the N48 sintered NdFeB magnet produced according to traditional steps.

[0043] For the new type of cerium iron boron rare earth magnet, the weight percentages of its components are: Pr-Nd: 23.5wt%, Ce: 7wt%, Al: 0.3wt%, Cu: 0.15wt%, B: 1.0wt%, Ti: 0.2wt%, and the rest is Fe.

[0044] For the N48 sintered NdFeB magnet produced according to the conventional steps, the weight percentages of its components are: Pr-Nd: 29wt%, Ce: 0wt%, Al: 0.2wt%, Gd: 1.5wt%, Zr: 0.2wt%, B: 1.0wt%, Cu: 0.15wt%, and the rest is Fe.

[0045] Table 1 shows the performance comparison of the new CeFeB rare earth magnet prepared according to the above formula and the N48 sintered NdFeB magnet (hereinafter referred to as N48 sintered NdFeB magnet) produced according to the traditional steps at a test temperature of 20°C.

[0046] Table 1

[0047]

[0048]

[0049] It can be seen that the remanence, magnetic coercivity, intrinsic coercivity, maximum magnetic energy product and squareness of the new Cerium Iron Boron rare earth magnet are better than those of N48 sintered NdFeB magnet.

[0050] According to the unit price of each raw material in August 2024, it can be calculated that the price of each kilogram of the new cerium iron boron rare earth magnet is 121.19 yuan, while the price of each kilogram of N48 sintered neodymium iron boron magnet is 149.18 yuan. It can be concluded that the cost of the new cerium iron boron rare earth magnet is 28.5 yuan / kilogram lower than that of the N48 sintered neodymium iron boron magnet, and the cost is reduced by 23%.

[0051] The embodiment of the three-stage aging process for improving coercivity provided by the present invention is as follows:

[0052] like Figure 1 As shown, the three-stage aging process for improving coercivity includes the following steps:

[0053] S1: Weigh the raw materials: weigh the raw materials according to claim 1 according to weight percentage, wherein Pr-Nd: 16-24wt%, Ce: 6-12wt%, Zr: 0-0.5wt%, Al: 0-1wt%, Cu: 0-0.5wt%, B: 0.9-1.1wt%, Co: 0-1.2wt%, Ti: 0-0.3wt%, Gd: 0-3wt%, and the rest is Fe;

[0054] S2: Melting castings: Put the raw materials in step S1 into a vacuum quick-setting furnace in order, let them stand after they are fully melted, and then cast them into scaly castings. When the casting temperature is lower than 40°C, collect the castings for later use;

[0055] S3: Hydrogen crushing and grinding: using a hydrogen crushing furnace to hydrogen crush the casting to obtain magnetic powder;

[0056] S4: Magnetic powder molding: molding the magnetic powder in a fully automatic magnetic field molding machine to obtain a compact;

[0057] S5: Sintering: The green compact is sintered in a vacuum sintering furnace, the sintering temperature is T1, the sintering time is t1, and the aging treatment is performed after the sintering treatment is completed. The heat treatment temperature of the primary aging treatment is T2, and the heat treatment time is t2. The heat treatment temperature of the secondary aging treatment is T3, and the heat treatment time is t3. The heat treatment temperature of the tertiary aging treatment is T4, and the heat treatment time is t4, wherein T2>T3>T4. After the tertiary aging treatment, the obtained green compact is cooled, and after being cooled to T5, a novel cerium-iron-boron rare earth magnet is obtained.

[0058] Among them, the sintering temperature T1 is 1020-1100°C, the sintering time t1 is 3-5h, the heat treatment temperature T2 is 870-950°C, the heat treatment time t2 is 2-3h, the heat treatment temperature T3 is 700-800°C, the heat treatment time t3 is 2-4h, the heat treatment temperature T4 is 420-460°C, and the heat treatment time t4 is 4-6h.

[0059] When the raw materials are melted, the preheating time of the vacuum rapid solidification furnace is t5, the melting temperature is T6, and the melting time is t6.

[0060] Specifically, the preheating time t5 is 30 to 40 minutes, the melting temperature T6 is 1350 to 1550° C., and the melting time t6 is 40 to 45 minutes.

[0061] During the hydrogen crushing process, the casting is hydrogen crushed in a hydrogen crushing furnace to obtain magnetic powder, which is then ground into 2.5-3.5μm magnetic powder by air flow mill and stirred in a three-dimensional mixer for a stirring time of t7. After stirring, it is placed in a stainless steel barrel and flushed with high-purity nitrogen for standby use.

[0062] Specifically, the stirring time t7 is 1 to 3.5 hours.

[0063] When the magnetic powder is formed in the full-automatic magnetic field forming press, the magnetic field intensity of the full-automatic magnetic field forming press is B, the forming pressure is P, and the holding time is t8.

[0064] Specifically, the magnetic field intensity B is 1.8 T, the molding pressure P is 4-8 MPa, and the holding time t8 is 30 s.

[0065] It should be noted that before each stage of aging treatment, the pressed blanks must be air-cooled to below 70°C.

[0066] According to the above description of this specification, those skilled in the art may also understand that the terms used below, such as "up", "down", "front", "back", "left", "right", "width", "horizontal", "top", "bottom", "inside", "outside" and the like, which indicate orientation or positional relationships, are based on the orientation or positional relationships shown in the drawings of this specification, and are only for the purpose of facilitating the explanation of the scheme of the present invention and simplifying the description, rather than explicitly or implicitly indicating that the devices or elements involved must have the specific orientation, be constructed and operated in a specific orientation. Therefore, the above-mentioned orientation or positional relationship terms cannot be understood or interpreted as limitations on the scheme of the present invention.

[0067] In addition, in the description of this specification, “plurality” means at least two, for example, two, three or more, etc., unless otherwise clearly and specifically defined.

Claims

1. A new type of cerium iron boron rare earth magnet, characterized in that: The invention comprises the following components: praseodymium-neodymium (Pr-Nd), cerium (Ce), zirconium (Zr), aluminum (Al), copper (Cu), boron (B), cobalt (Co), titanium (Ti), gadolinium (Gd), and iron (Fe), wherein Pr-Nd: 16-24wt%, Ce: 6-12wt%, Zr: 0-0.5wt%, Al: 0-1wt%, Cu: 0-0.5wt%, B: 0.9-1.1wt%, Co: 0-1.2wt%, Ti: 0-0.3wt%, Gd: 0-3wt%, and the rest is Fe.

2. A three-stage aging process for increasing coercivity, characterized in that: The steps include: S1: Weighing raw materials: Weighing the raw materials according to claim 1 according to weight percentage, wherein Pr-Nd: 16-24wt%, Ce: 6-12wt%, Zr: 0-0.5wt%, Al: 0-1wt%, Cu: 0-0.5wt%, B: 0.9-1.1wt%, Co: 0-1.2wt%, Ti: 0-0.3wt%, Gd: 0-3wt%, and the rest is Fe; S2: Melting castings: Put the raw materials in step S1 into a vacuum quick-setting furnace in order, let them stand after they are fully melted, and then cast them into scaly castings. When the casting temperature is lower than 40°C, collect the castings for later use; S3: Hydrogen crushing and grinding: using a hydrogen crushing furnace to hydrogen crush the casting to obtain magnetic powder; S4: Magnetic powder molding: molding the magnetic powder in a fully automatic magnetic field molding machine to obtain a compact; S5: Sintering: The green compact is sintered in a vacuum sintering furnace, the sintering temperature is T1, the sintering time is t1, and the aging treatment is performed after the sintering treatment is completed. The heat treatment temperature of the primary aging treatment is T2, and the heat treatment time is t2. The heat treatment temperature of the secondary aging treatment is T3, and the heat treatment time is t3. The heat treatment temperature of the tertiary aging treatment is T4, and the heat treatment time is t4, wherein T2>T3>T4. After the tertiary aging treatment, the obtained green compact is cooled, and after being cooled to T5, a novel cerium-iron-boron rare earth magnet is obtained.

3. The three-stage aging process for improving coercivity according to claim 2, characterized in that: The sintering temperature T1 is 1020-1100° C., and the sintering time t1 is 3-5 hours.

4. The three-stage aging process for improving coercivity according to claim 3, characterized in that: The heat treatment temperature T2 is 870-950°C, the heat treatment time t2 is 2-3h, the heat treatment temperature T3 is 700-800°C, the heat treatment time t3 is 2-4h, the heat treatment temperature T4 is 420-460°C, and the heat treatment time t4 is 4-6h.

5. The three-stage aging process for increasing coercivity according to any one of claims 2 to 4, characterized in that: The preheating time of the vacuum rapid solidification furnace is t5, the melting temperature is T6, and the melting time is t6.

6. The three-stage aging process for improving coercivity according to claim 5, characterized in that: The preheating time t5 is 30 to 40 minutes, the smelting temperature T6 is 1350 to 1550° C., and the smelting time t6 is 40 to 45 minutes.

7. The three-stage aging process for increasing coercivity according to any one of claims 2 to 4, characterized in that: The casting sheet is subjected to hydrogen crushing treatment in a hydrogen crushing furnace to obtain the magnetic powder, and then the magnetic powder is ground into 2.5-3.5 μm magnetic powder by air flow mill and stirred in a three-dimensional mixer for a stirring time of t7. After the stirring is completed, it is placed in a stainless steel barrel and flushed with high-purity nitrogen for standby use.

8. The three-stage aging process for improving coercivity according to claim 7, characterized in that: The stirring time t7 is 1 to 3.5 hours.

9. The three-stage aging process for increasing coercivity according to any one of claims 2 to 4, characterized in that: The magnetic field strength of the fully automatic magnetic field forming press is B, the forming pressure is P, and the holding time is t8.

10. The three-stage aging process for improving coercivity according to claim 9, characterized in that: The magnetic field intensity B is 1.8T, the molding pressure P is 4-8MPa, and the holding time t8 is 30s.

Citation Information

Patent Citations

  • A high performance cerium iron boron magnet and its preparation method

    CN113643870B